Analysis of promoter regions for the spinach chloroplast rbcL, atpB and psbA genes. - Gruissem, W (1985)
A promoter-deletion derivative of the spinach trnM2 gene was used for the identification and characterization of the promoter regions for the spinach chloroplast RuBisCo large subunit (rbcL), ATPase beta-subunit (atpB) and QB-polypeptide (psbA) genes. The DNA sequences 5' upstream from the transcriptional start sites of these genes share homology with the ctp1 and ctp2 arrangement found for the trnM2 transcription unit and the canonical Escherichia coli '-10' and '-35' promoter regions. Synthetic DNA fragments of approximately 40-bp regions, including the defined transcriptional start sites and proximal residues, from rbcL, atpB and psbA, were fused to the trnM2 deletion mutant 51. The promoter-fusion constructs direct the correct transcription of tRNAMet2 in the chloroplast extract with distinct efficiencies. The ctp1- and ctp2-like elements in the trnM2, rbcL and psbA promoter regions can be interchanged to yield functional chimeric promoters of varying strengths. As a result, ctp1 sequences from atpB and psbA, trnM2 and rbcL, respectively, can be ordered TTGACA greater than TTGCTT greater than TTGCGC with respect to their intrinsic strengths. Single base pair changes were introduced into the ctp2-like element in the psbA promoter region. In analogy to similar base pair changes which lower promoter efficiency in E. coli, these mutations result in reduced transcription levels in the chloroplast extract. The data are consistent with a prokaryotic model for chloroplast promoter function.